KOMPARASI PERUBAHAN ASPEK SOSIAL EKONOMI PADA PENGHUNI RUMAH SUSUN PASCA PENANGANAN SQUATTER DI KOTA SURAKARTA - Khizam Deby Kurniawan; Ana Hardiana; Rufia Andisetyana Putri (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2015)
City has main attraction for livable. The public has the view that a town has a comprehensive facilities , good accessibility , a broad field of work and so on. This matter causes population growth developments in the city, because people migrating to the city livelihood for the sake of more worthy. The increasing population is not balanced with the service especially in the field of housing the city settlement that will appear squatter. So that the squatter need to be handled, in general the handling of having two pattern handling squatter approach , that is a pattern on-site and off-site. On site pattern is a problem handling squatter location without move to another region but with providing a place of decent housing. While off site pattern is handling by moving the squatter to the regions and with the status of land was legal. In fact both handling is to improve social life and economic society. One of squatter handling in Surakarta is build a low cost apartment. The limited land in Surakarta is one of the reason to build a low cost apartment in the Surakarta City for handling squatter. Based on issues, this research knowing comparisons of socio-economic change in the low cost apartment post-handling squatter. The method is applicable in weighting analysis methods in identifying the social economy at low cost apartment in Surakarta. This result oh the research re the comparisons of socioeconomic aspects of changes on residents after handling squatter in Surakarta can be seen that in Begalon I low cost apartment experienced a medium increase, while in Begalon II low cost apartment and Semanggi low cost apartment increased low. So that the change in the economic and social aspect of Begalon I low cost apartment with on site pattern has the higher than Begalon II low cost apartment and Semanggi low cost apartment with off site pattern. Keywords: low cost apartment, socioeconomic aspects, squatter